Evolução, avaliação e validação do software RoboEduc - Barros, Renata Pitta (2011)
Considering the transition from industrial society to information society, we realize that the digital training that is addressed is currently insufficient to navigate within a digitized reality. As proposed to minimize this problem, this paper assesses, validates and develops the software RoboEduc to work with educational robotics with the main differential programming of robotic devices in levels, considering the specifics of reality training . One of the emphases of this work isthe presentation of materials and procedures involving the development, analysis and evolution of this software. For validation of usability tests were performed, based on analysis of these tests was developed version 4.0 of RoboEduc